O10.6 Clearance of mycoplasma genitalium and trichomonas vaginalis among adolescents and young adults with pelvic inflammatory disease: results from the tech-n study. (8th July 2017) - Trent, Maria; Perrin, Jamie; Butz, Arlene; Anders, Jennifer; Huettner, Steven; Gaydos, Charlotte
Abstract : Introduction: While the broad-spectrum antibiotics recommended for treatment of pelvic inflammatory disease (PID) effectively treats Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT), coverage may be inadequate for Mycoplasma genitalium (MG) and Trichomonas vaginalis (TV). Untreated MG and TV may result in vaginal dysbiosis, increasing the risk for recurrent STIs and HIV. The objective of this study is to evaluate longitudinal MG and TV outcomes compared with GC/CT outcomes over the 90 day following treatment. Methods: 259 Female AYA aged 13–25 years with mild-moderate PID enrolled in a randomised trial of a technology enhanced community health nursing study designed to prevent STIs after PID. Participants completed audio computer-assisted self-interviews and provided vaginal specimens at baseline, 30 days and 90 days and were notified and referred for treatment for positive results. Generalised estimating equations were used to measure changes in the prevalence of MG and TV compared with GC/CT over time. Results: At baseline, 29% were positive for CT or GC at baseline (25% CT and 8% GC), 19% for MG, and 16% for TV. Ninety-four percent of the effective sample was retained at 90 days and 44% reported completing all medication doses. At 30 days, 17 (8%) of women were positive for CT or GC, while 36 (17%) were MG positive, and 22 (10%) were positive for TV. At 90 days, 13 (6%) were positive for CT or GC, 39 (18%) for MG, and 30 (14%) for TV. GC/CT infection was declining on average over time (odds ratio 0.48, 95% CI 0.36 to 0.63 per additional month). MG was not significantly changing over time (odds ratio 0.94, 95% CI 0.84 to 1.05), at a different rate than GC/CT (p<0.001). TV was also consistent over time (odds ratio 0.92, 95% CI 0.78 to 1.09), also at a different rate than GC/CT (p<0.001). Conclusion: Youth treated with the recommended syndromic management protocols clear infection with GC/CT, but often have recurrent, persistent, and/or new MG/TV infections during the 90 day post-PID follow-up period.